Using functional calibration methods to estimate the midfoot joint center in planovalgus feet - Campos, Sarah; Salami, Firooz; Götze, Marco; Gather, Katharina Susanne; Wolf, Sebastian Immanuel (Journal of biomechanics, 2025)
In order to improve the understanding foot function in the presence of planovalgus foot deformity, functional joint center determination is applied to the ankle and midfoot for application in 3D-gait analysis. Gait data of 36 patients with planovalgus (PV) foot deformity as well as of 33 typically developing (TD) subjects were collected using foot markers according to the Heidelberg Foot Measurement method. During single-limb stance subjects performed a circular movement of the foot and ankle (CIR) by drawing a circle with the hallux in the air. Midfoot joint center location as well as kinematics was calculated based (a) on functional calibration, (b) via a simple midpoint approach, and (c) via linear regression. All typically developing participants were able to perform the CIR movement with sufficient ROM for calibration whereas 10 % of the participants with idiopathic PV foot deformity and 72 % of the participants with a neurogenic PV foot were not able to perform this movement adequately. Nevertheless, the regression approach led to almost the same location of the midfoot joint center compared to the functional method with similar kinematics. PV feet show substantially larger Forefoot/Hindfoot flexion and Forefoot/Hindfoot adduction in gait compared to TD feet. On top, feet with neurologic background show reduced ROM of these angles in gait. The CIR movement task may prove useful in future studies monitoring active ranges of ankle and midfoot motion since the kinematics of this task may also be directly assessed via the proposed regression approach.
Online verfügbar: 2. Januar 2025, Artikelversion: 9. Januar 2025
Gesehen am 24.07.2025